Maternal and Neonatal Outcomes After Assisted Reproductive Technology: A Retrospective Cohort Study in China - Tai, Wen; Hu, Lingmin; Wen, Juan (Frontiers in Medicine, 2022)
Background: With the progress of assisted reproductive technology (ART) and the increasing number of ART pregnancy, its safety has become the focus of attention. The present study aimed to explore the associations of ART pregnancy with maternal and neonatal outcomes, as compared with naturally pregnancy. Methods: This retrospective cohort study included all pregnant women who delivered at Women’s Hospital of Nanjing Medical University in 2011-2020. We compared maternal characteristics and pregnancy outcomes between group of ART pregnancy and group of naturally pregnancy using Logistic regression adjusted for confounders. Results: A total of 13,604 ART pregnancies and 198,002 naturally pregnancies were included. The proportion of ART pregnancies has increased every year for the past 10 years, peaking in 2020 (9.0%). Multivariable logistic regression analysis showed that the risks of gestational diabetes, preeclampsia, moderate or severe anemia, liver-related diseases, thyroid-related diseases, preterm birth, placenta previa, postpartum hemorrhage, and cesarean section were significantly increased in ART pregnancy. For neonatal outcomes, women conceived by ART were more likely to have twins or multiples, and the risk of stillbirth or abnormal development was also significantly increased. When restriction to singletons, these risks were reduced. And the effects of ART on the risk of premature rupture of membrane, cord entanglement, intrapartum fever, cesarean section, and stillbirth or abnormal development were more pronounced in singletons pregnancies compared with that in pregnancies of twins or multiples. Conclusions: Women conceived by ART were at increased risks of several adverse pregnancy outcomes compared with women conceived naturally. Multiple pregnancies could partly explain this phenomenon. For ART pregnancy, prenatal and intrapartum monitoring should be strengthened, and neonatal outcomes should be closely observed.